Human Resource Management for School Effectiveness - Balogun, Babatunde Nurudeen (International Journal of Educational Management, 2021)
The success of an organization to a large extent depend on the human performance and the human performance is a dictate of the knowledge, skills, values and behaviours of individual staff of the organization. The human resource management is being considered as one of the basic tools for improving staff quality that will enhance the efficiency and effectiveness of secondary schools being formal organization. The role of secondary school in the accomplishment of the overall goals of education in Nigeria cannot be over-emphasised. The paper discusses human resource management with reference to public secondary schools in Nigeria, roles of human resource management in enhancing the effectiveness of public secondary schools in Nigeria and challenges of human resource management in the public secondary schools. To overcome these challenges and enhance public secondary school effectiveness in Nigeria, the paper recommends that secondary school should be adequately funded, regular and adequate supervision of schools, establishment of coordinating agency or body, improvement of recruitment procedures, regular and continuous training of staffs and effective maintenance of disciplinary mechanism.